VD_FINDINFO HC / 2015 / 761 vom 8. Juli 2015 - VD Tribunal cantonal (2015)
DIVORCE, CONJOINT, OBLIGATION D'ENTRETIEN, REVENU DE LA FORTUNE, REVENU HYPOTHÉTIQUE | 125 al. 1 CC, 125 al. 2 CC, 308 al. 1 let. a CPC (CH)